Peran Pemerintah Daerah Dalam Pengembangan Industri Kecil Dan Menengah (IKM) Berbasis Agribisnis (Study Pada Dinas Perindustrian, Perdagangan dan Pasar Kabupaten Malang) - Rifky Wicaksono (Jurnal Administrasi Publik, 2016)
Abstract. The Role of Local Government in the Development of Small and Medium Industries Based Agribusiness (Studies in the Department of Industry, Trade and Market Malang Regency). Malang Regency is one of the potential areas for development of Small and Medium Industry based agribusiness. Judging from the role of government as a facilitator, regulator and catalyst. The results showed, the regional government has performs various roles and good effort in developing Small and Medium Industry based agribusiness in Malang Regency. As a facilitator, the Government provided assistance through a variety of education and training, giving industrial equipment aid and giving promotion for the product. As a regulator, the Government create one village one product policy for each village and provide convenience for industrial permit. Meanwhile, as a catalyst, local government facilitate industry owner to manage apply permit for Intellectual Property Rights (IPR) for Small and Medium Industries in Malang Regency.The supporting factors, the local government giving support and motivation for the small and medium industry based on agribusiness, good quality of the products and the availability of abundant raw materials. Whereas the limiting factor are in production labor, the technology that used for Small and Medium Industry based agribusiness in Malang Regency still simple, limited marketing and product distribution issues. Keyword :the role of local government, in the development of small and medium industries based agribusiness Abstrak: Peran Pemerintah Daerah Dalam Pengembangan Industri Kecil Menengah Berbasis Agribisnis (Studi Pada Dinas Perindustrian,Perdagangan,dan Pasar Kabupaten Malang). Kabupaten Malang adalah salah satu daerah potensial untuk Pengembangan Industri Kecil dan Menengah berbasis agribisnis. Ditinjau dari peran pemerintah sebagai fasilitator,regulator dan katalisator. Hasil penelitian menunjukkan, Pemerintah Daerah telah melakukan berbagai peran dan upaya dengan baik guna mengembangkan Industri Kecil dan Menengah berbasis agribisnis di Kabupaten Malang. Sebagai Fasilitator, Pemda memberikan bantuan melalui berbagai pendidikan dan pelatihan, bantuan peralatan industri dan membantu mempromosikan produk. Sebagai Regulator, Pemda memberikan kebijakan satu desa satu produk untuk setiap desa dan memberikan kemudahan dalam hal perijinan Industri. Sedangkan sebagai Katalisator, Pemda memberikan fasilitasi bantuan kepengurusan Hak atas Kekayaan Intelektual (HAKI) bagi Industri Kecil dan Menengah di Kabupaten Malang. Faktor pendukung pengembangan IKM yaitu adanya dukungan dan motivasi penuh dari pemerintah daerah, produk-produk ikm yang berkualitas, dan tersedianya bahan baku yang melimpah. Sedangkan pada faktor penghambat diantaranya adalah pada tenaga kerja produksi, teknologi yang masih sederhana, pemasaran terbatas dan masalah distribusi produk. Kata Kunci : peran pemerintah daerah, dalam pengembangan industri kecil menengah berbasis agribisnis